Antidepressant effect of Gentiana olivieri Griseb. in male rats exposed to chronic mild stress. Issue 1 (1st January 2020) - Berk, Ahmet; Yılmaz, İsmet and Abacıoğlu, Nurettin and Kaymaz, Mustafa Bahadır and Karaaslan, Merve Gökşin and Kuyumcu Savan, Ebru
ABSTRACT: Background : The flowering parts of Gentiana olivieri, known as 'Afat' in the southeastern Anatolia region of Turkey, are used as a tonic, an appetizer, and for the treatment of several mental disorders, including depression. The purpose of this study is to investigate the antidepressant effect of G. olivieri ethanol extract (GOEE) in a chronic mild stress-induced rat model, which was used to mimic a depressive state in humans, and to compare the effect with that of imipramine. Methods : Male Sprague-Dawley rats were randomly divided into six groups: control, stress, treated with imipramine (positive control) and treated with GOEE at three different (200, 500, 1000 mg/kg) doses groups. The rats in all groups, except the control group, were exposed to chronic mild stress. At the end of the 3-week experimental period, biochemical and behavioral parameters were examined. Results : The results showed that treatment with GOEE or imipramine significantly improved rats' sucrose consumption which was diminished by chronic mild stress, restored serum levels of corticosterone and proinflammatory cytokines (interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α)), prevented the increase of liver index of rats. Moreover, in the hippocampus tissue, decreased serotonin and noradrenaline levels were significantly increased by treatment with GOEE or imipramine, and antioxidant parameters (thiobarbituric acid reactive substances (TBARS), superoxide dismutase (SOD), and glutathione (GSH)) were significantly improved by treatment with GOEE though not with imipramine. Conclusion : The data demonstrate that G. olivieri may exert its antidepressant activity by improving monoaminergic system disorders, and by favorably affecting the antioxidant, inflammatory and the endocrine mechanisms.